THE PRINCIPLES OF BUILDING A PEOPLE’S DEMOCRATIC STATE ACCORDING TO PRESIDENT HO CHI MINH DURING THE WAR OF RESISTANCE AGAINST FRENCH COLONIALISM (1945–1954) - Dinh Le Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
Over 15 years (1930–1945), under the leadership of the Party, the Vietnamese nation overcame numerous challenges to seize power in the 1945 August Revolution and establish the Democratic Republic of Vietnam. In this article, the author synthesizes and systematizes materials, studies, evaluates, and draws out some fundamental principles that the Party and President Ho Chi Minh applied in the process of building a state of the people, laying the foundation for the long-term revolutionary cause of the Vietnamese people. Vietnam has favorable conditions for comprehensive national development in the context of renewal and deep international integration. However, difficulties and challenges persist, external forces oppose the state-building efforts, and the degeneration and corruption of some officials and Party members have significantly affected the leadership role and credibility of the Party and government. Therefore, understanding the principles in building and organizing the government of the Democratic Republic of Vietnam under the direct leadership of President Ho Chi Minh during the First Resistance War (1945–1954) is certainly of practical significance, providing further experience for the construction and organization of the Socialist Republic of Vietnam, a state of the people, by the people, and for the people in the current context of national development.